Guidelines for determining the probability of ignition of a released flammable mass (Wiley., 2014)
"Complemented by an estimating tool spreadsheet based on a fixed set of chemicals to assist in all siting studies, [Guidelines for determining the probability of ignition of a released flammable mass] converts a "best guess" to a calculated value based on available information and current technology. The text provides a technology-based approach to deriving the probability that a flammable mass will find an ignition source and ignite. It offers valuable information in the development of a facility's Emergency Response Plan"--